Ethnomycological study on wild mushrooms in Pu'er Prefecture, Southwest Yunnan, China - Ran Wang; Mariana Herrera; Wenjun Xu; Peng Zhang; Jesús Pérez Moreno; Carlos Colinas; Fuqiang Yu (BMC, 2022)
Abstract Background Yunnan is rich in fungal diversity and cultural diversity, but there are few researches on ethnomycology. In addition, extensive utilization of wild edible fungi (WEF), especially the ectomycorrhizal fungi, threatens the fungal diversity. Hence, this study aims to contribute to the ethnomycological knowledge in Pu'er Prefecture, Yunnan, China, including information on the fungal taxa presented in markets and natural habitats, with emphasis in ectomycorrhizal fungi (EMF). Methods Semi-structured interviews with mushroom vendors in markets and with mushroom collectors in natural habitats were conducted. Information related to local names, habitat, fruiting time, species identification, price, cooking methods and preservation methods of wild edible mushrooms were recorded. Wild edible fungi were collected from forests, and morphological and molecular techniques were used to identify fungal species. Results A total of 11 markets were visited during this study. The 101 species collected in the markets belonged to 22 families and 39 genera, and about 76% of them were EMF. A wealth of ethnomycological knowledge was recorded, and we found that participants in the 45-65 age group were able to judge mushroom species more accurately. Additionally, men usually had a deepest mushroom knowledge than women. A total of 283 species, varieties and undescribed species were collected from natural habitats, and about 70% of them were EMF. Mushroom species and recorded amounts showed correspondence between markets and the natural habitats on different months. Conclusion The present study shows that Pu'er Prefecture is rich in local mycological knowledge and fungal diversity. However, it is necessary to continue the research of ethnomycological studies and to design and conduct dissemination of local knowledge in order to preserve it, since it currently remains mainly among the elderly population.